Those Who Leave and Those Who Feel Left: The Complexity of Quaker Disaffiliation - Dandelion, Pink (Journal of contemporary religion, 2002)
Unprogrammed Friends (Quakers) in Britain provide an interesting counter-example within the sociology of religion, particularly with regard to their patterns of believing and belonging. Due to its permissive belief patterns and conformist behavioural patterns, the group has been described in terms of a 'double-culture', as a group which behaves as both sect and denomination in alternate spheres of church life. The paper reports on a study of British Quakers who have resigned their Membership in the last five years. Quakers leave either because they are 'de-convinced' or because, in a group which places emphasis on continuing revelation, they are grieving the loss of what has passed before. A third type resigns because they feel the group is too slow to support new revelation. In these latter two cases, the disaffiliated feel left by the group. This typology is placed across the concept of the double-culture to give six types of ex-Quaker and to show how conservative or progressive thinking in each sphere of the double-culture may lead to different patterns of resistance to resignation from the group. Recent work on the Quaker group as an 'implicit sect' is briefly considered to examine how this new thinking affects the typology of church-leavers. It is suggested that the extended typology of the disaffiliated challenges conceptions of the disaffiliated as a single group and that it could be usefully employed in studying other religious groups.